STRUCTURE OF GREAT NUMBER OF NEVANLINN IMPERFECT VECTORS FOR WHOLE CURVES WITH LINEARLY DEPENDENT COMPONENTS - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is shown that structure of great number of Nevanlinna defect vectors for the whole curve of complete order with linearly dependent components similar to the structure for the ordinary entire curve of finite order.